Compressed air energy storage for large-scale renewable energy systems for a case study of Egyptian grid - Ramadan, Omar (2016)
All across the world, attention is turning to renewable energies to serve at least as a partial substitute to fossil fuels in the global energy mix, braking the latter’s depletion and providing a greener solution for a more sustainable future. However, the intermittent nature of most renewable energy sources, wind and solar in particular, raises major concerns over the integration of these technologies, on a large scale, to grid systems. This thesis focuses on large-scale renewable energy storage systems, primarily compressed air energy storage (CAES) systems, which are particularly well suited for renewable energy applications. CAES can play a major role in shaping the future of renewable energy systems for not only can it bring load levelling to the system, but it can also add substantial value by providing ancillary services to the grid. The main focus of this research is adiabatic CAES which endeavours to minimize the use of natural gas by using recuperators and thermal energy storage systems, where the heat from the air during the compression stages is absorbed by a heat transfer fluid, stored, and then supplied back during the expansion process. This project aimed to explore the potential of CAES systems as an energy storage technology for large-scale grid integrated renewable energy system. A computer model was developed to size the different components in the CAES system and also to predict the operational performance of the CAES system for different conditions using MATLAB programming. The thermal energy storage of an adiabatic CAES system was optimized using CFD analysis and experimental testing of the thermal energy storage system was carried out to validate the models. Also, an economic study was performed to assess the feasibility of the CAES system based on a case study of the Egyptian grid. The dynamic simulation of a novel configuration of an adiabatic CAES system showed that the system can achieve improved performance compared to existing CAES plants, while the economic study showed that CAES can improve the economics of a wind farm, at least by the standards of our chosen case study location